Hachalu Hundessa protests (Ethiopia) - Voidly (Voidly Global Censorship Index, 2020)
CRITICAL severity censorship detected in Ethiopia. Data sourced from OONI.
Censorship Incident ID: ET-2020-0001. Severity: critical. Confidence: 90%